2021
DOI: 10.1002/joc.7290
|View full text |Cite
|
Sign up to set email alerts
|

The role of teleconnection patterns in the variability and trends of growing season indices across Europe

Abstract: Teleconnection patterns affect the weather and climate on both interannual and decadal timescales which in turn affects various socio-economic sectors such as agriculture. We use three climate indices based on E-OBS data from the INDECIS dataset (growing season onset [ogs10], growing season rainfall [gsr] and growing season temperature [ta_o]) to assess the interannual variability and trends over 1950-2017 associated with four teleconnection patterns (North Atlantic Oscillation [NAO], East Atlantic pattern [EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Our study reveals that the NAO significantly influenced temperature indices in Serbia during the winter and summer but less than the EA pattern. Our results are in agreement with the findings of Craig and Allan (2021), who found that the NAO correlates significantly with growing season onset for all regions in Europe, although the EA dominates in continental regions. A significant influence of the EA pattern on temperature in summer is confirmed in previous studies for Serbia (Unkašević and Tošić, 2013; Knežević et al ., 2014; Ruml et al ., 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study reveals that the NAO significantly influenced temperature indices in Serbia during the winter and summer but less than the EA pattern. Our results are in agreement with the findings of Craig and Allan (2021), who found that the NAO correlates significantly with growing season onset for all regions in Europe, although the EA dominates in continental regions. A significant influence of the EA pattern on temperature in summer is confirmed in previous studies for Serbia (Unkašević and Tošić, 2013; Knežević et al ., 2014; Ruml et al ., 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Lim (2015) found that the positive (negative) EA/WR phase is associated with a strong warming (cooling) over Western Europe and Northwestern Africa whereas it is associated with cooling (warming) in far Eastern Europe, Northeastern Africa and the Middle East in winter. Linking the variability in climate indices to teleconnection patterns can help us to understand how various aspects of the climate are changing in response to changes in atmospheric circulation (Craig and Allan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At an annual scale SCAND and AMO are considered to be the driving factors. At a seasonal scale El Niño‐Southern Oscillation (ENSO) and NAO are considered to have influences on summer and winter precipitation, respectively (Craig & Allan, 2021; Seager et al., 2020; Uvo, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The wavelet coefficients of the first periodicity have higher correlation coefficient values for all stations of five regions. The wavelet coefficients of the second (Craig & Allan, 2021;Seager et al, 2020;Uvo, 2003).…”
Section: Table 6 Maximal Information Coefficient (Mic) Values Between...mentioning
confidence: 99%
“…12) (Hurrell, 1995;Hurrell and Van Loon, 1997). The modern (non-simulated) NAO exists in all seasons (Craig and Allan, 2022) but is more prominent and stable in winter. A well-developed dipole pressure gradient between the Icelandic Low and Azores High in its positive phase induces strong westerlies and northerly storm tracks that transport air masses from the eastern Atlantic towards Central Europe.…”
Section: Impacts Of the Diachronous Surface Uplift On Atmospheric Flo...mentioning
confidence: 98%